Insect trehalase: physiological significance and potential applications - Shukla, Ekta; Thorat, Leena J.; Nath, Bimalendu B.; Gaikwad, Sushama M. (Glycobiology, 2015)
Trehalose, a non-reducing disaccharide, is widespread throughout the biological world. It is the major blood sugar in insects playing a crucial role as an instant source of energy and in dealing with abiotic stresses. The hydrolysis of trehalose is under the enzymatic control of trehalase. The enzyme trehalase is gaining interest in insect physiology as it regulates energy metabolism and glucose generation via trehalose catabolism. The two forms of insect trehalase namely, Tre-1 and Tre-2, are important in energy supply, growth, metamorphosis, stress recovery, chitin synthesis and insect flight. Insect trehalase has not been reviewed in depth and the information available is quite scattered. The present mini review discusses our recent understanding of the regulation, mechanism and biochemical characterization of insect trehalase with respect to its physiological role in vital life functions. We also highlight the molecular and biochemical properties of insect trehalase that makes it amenable to competitive inhibition by most glycosidase inhibitors. Due to its crucial role in carbon metabolism in insects, application of inhibitors against trehalose can form a promising area towards formulating strategies for insect pest control.
Keywords: carbohydrate metabolism; glycosidase inhibitor; glycoside hydrolase; trehalase; trehalose

Ipso-cyclization via a dienone-phenol rearrangement of alkynyloxy cyclohexadienones for the synthesis of oxaspiro[4.5]trienones - Rai, Archana; Kundu, Ananya I.; Shukla, Ekta; Das, Utpal (Journal of Organic Chemistry, 2025)
Herein, we present a convenient method to access oxaspiro[4.5]trienone compounds from alkynyloxy cyclohexadienones. The reactions are catalyzed by Lewis/Bronsted acids, yielding the desired products in moderate to good yields under very mild reaction conditions. The process, which involves a dienone-phenol rearrangement, is characterized by its simplicity and the absence of any additional activators. The synthesis of the oxaspiro[4.5]trienone compounds is amenable to gram-scale reactions along with subsequent product transformations, making this approach practical and attractive.